PENGARUH MODEL EVALUASI TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Komarudin, - (2012)
Selama ini untuk memahami keberhasilan siswa dalam pembelajaran pendidikan jasmani, guru cenderung menggunakan evaluasi tradisional berupa tes standar atau tes yang dibuat oleh guru. Tes tersebut cenderung mengevaluasi cuplikan-cuplikan perilaku siswa yang pelaksanaannya terlepas dari konteks belajar, mengajar, dan evaluasi. Selanjutnya, pelaksanaan evaluasi belum terintegrasi dengan proses pembelajaran sehingga hasil belajar lebih terfokus pada hasil akhir yang tidak melibatkan proses pembelajaran, padahal dalam proses pembelajaran siswa sering menampilkan berbagai bentuk keterampilan yang sangat mendukung terhadap hasil akhir. Ketimpangan itu diperkuat pula oleh praktik pengajaran yang mengabaikan perkembangan domain kognitif dan afektif, sehingga evaluasi tersebut tidak menggambarkan kemajuan hasil belajar siswa secara menyeluruh. Penerapan model evaluasi portofolio diharapkan menjadi langkah strategis dalam mengevaluasi hasil belajar siswa secara menyeluruh sehingga guru pendidikan jasmani benar-benar dapat memotret seluruh profil hasil belajar siswa. Penelitian ini menggunakan metode kuasi eksperimen dengan disain "the matching only pretest-posttest control group design." Populasi adalah siswa kelas delapan SMP YAS Kota Bandung sebanyak enam kelas, dan sampelnya adalah kelas A dan kelas D yang diambil dengan menggunakan cluster random sampling. Melalui random dihasilkan kelas A sebagai kelompok eksperimen dan kelas D sebagai kelompok kontrol. Teknik pengolahan dan analisis data menggunakan teknik MANOVA pada taraf signifikansi =537; 0,05. Hasil penelitian menunjukkan bahwa: (1) model evaluasi portofolio lebih efektif dibandingkan dengan model evaluasi tradisional terhadap hasil belajar domain kognitif; (2) model evaluasi portofolio lebih efektif dibandingkan dengan model evaluasi tradisional terhadap hasil belajar domain afektif; (3) model evaluasi portofolio lebih efektif dibandingkan dengan model evaluasi tradisional terhadap hasil belajar domain psikomotor; dan (4) model evaluasi portofolio lebih efektif dibandingkan dengan model evaluasi tradisional terhadap kebugaran jasmani siswa. Hasil penelitian tersebut direkomendasikan bahwa untuk memperoleh hasil belajar siswa secara komprehensif yang mencakup semua domain dalam pembelajaran pendidikan jasmani, model evaluasi portofolio dapat dijadikan sebagai alternatif untuk mengevaluasi dan mendukung peningkatan kualitas hasil belajar siswa dalam pembelajaran pendidikan jasmani di SMP. ABSTRACT KOMARUDIN. The Influence of Evaluation Model on the Results of Students' Learning in Physical Education Learning (A study on the Application of Portfolio Evaluation Model and Traditional Evaluation Model on the Result of Learning in the Domains of Cognitive, Affective, Psychomotor, Physical Fitness of YAS Junior High School in Bandung). A Dissertation. Postgraduate School of Indonesia University of Education. 2012. In order to understand students' learning mastery in physical education, teachers have so far applied traditional evaluation method in the form of standard test or tests that are made by teachers. Those tests tend to evaluate students' samples behavior, yet, its implementation is far from the contexts of teaching, learning and evaluation. Additionally, the evaluation has not been integrated with the learning process so that the results of the learning are focused more on its final achievement, disregarding the process of learning itself. Meanwhile, it is in the learning process that students perform their skills that eventually support the final results. Furthermore, this overlapping situation in the learning process is strengthened by the pattern of teaching that ignores the development of cognitive and affective domains. This results in the incomplete progress test as it cannot picture the students' progress as a whole. Portfolio evaluation model is expected to be one of the strategic steps in totally evaluating students' progress so that in teachers of Physical Health Education can illustrate students' profile entirely. This study employs quasi experiment with the matching only pretest-posttest control group design. Population is student group eight of YAS Junior High School in Bandung. The sample is group A and group D that by using cluster Randomly taken. Pass by random produced by A as a treatment group and D as a control group. The sample of every group consists of 46 students of YAS Junior High School in Bandung. Other than that, the data is collected by measuring students' learning result comprising cognitive, affective and psychomotor domains and physical fitness. After the data is collected, it is then analyzed using MANOVA with the significance level α 0.05. The results show that: (1) in the terms of cognitive domain, portfolio evaluation model is found to be more effective than the traditional one on the students' learning; (2) in the respect of affective domain, portfolio evaluation model is turned out to be more effectual than the traditional one on the students' learning; (3) in the regard of psychomotor domain, portfolio is more effective than the traditional one on the students' learning; (4) portfolio evaluation model is more effective than the traditional one on the students physical health. In addition, the study recommends that in order to comprehensively attain students' learning result in the learning of physical education in junior high school that comprises all domains, portfolio evaluation model can be utilized as an alternative evaluation to support the quality improvement of students' learning result.